The prefix seudo- is not a pseudoprefix - Martín García, Josefa (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This paper examines the formations in seudo- in order to show the prefixal nature of this morphological element. As the data show, seudo- presents characteristics similar to those that define prototypical prefixes. Thus, from its meaning as intensional adjective, seudo- develops readings related to resemblance, negation, and gradation. These new meanings of seudo- have a more abstract and relational character, which makes it possible to extend both its categorial selection by combining with adjectives and verbs, and its productivity.